Clinical Predictive Factors of Failure of Hysteroscopic Endometrial Ablation: Retrospective Cohort Study at a Tertiary University Hospital - Naser Al-Husban; Ala' Abukhalaf; Rama Nada; Lina Alqirem; Mohammad Alshrouf; Hedaieh Al-Husban (IMR Press, 2023)
Background: Endometrial ablation is a safe and effective minimally invasive surgical procedure. Despite the high success rate of endometrial ablation for heavy uterine bleeding management, some patients experience persistent symptoms after the procedure, necessitating a hysterectomy. The aim of this study is to determine the pre-operative clinical predictive factors of failure of endometrial ablation in the management of uterine bleeding. Methods: Retrospective cohort study of endometrial ablation procedures performed for treating heavy uterine bleeding. Results: Ninety five patients were included in the study. The failure rate was 24.2%. There was a statistically significant association between ablation failure and fluid deficit (p = 0.002) and intra-operative blood loss (p = 0.047). There was a statistically significant moderate association between adenomyosis (p = 0.003, φ = 0.37) and failed endometrial ablation. However, the age, body mass index (BMI), parity, number of miscarriages, number of cesarean sections, uterine length, endometrial thickness and procedure duration had no significant association with endometrial ablation. There was no significant relationship between the uterine abnormalities in general and the outcome of the endometrial ablation (p = 0.637). However, patients with combined adenomyosis and dysmenorrhea had a statistically significant association with outcome of the endometrial ablation (p = 0.016, φ = 0.28) and were more likely to have a failed endometrial ablation (crude odds ratio (COR) = 4.67, 95% confidence interval (CI), 1.35-16.09). Logistic regression to adjust for related factors revealed that the adenomyosis (adjusted odds ratio (AOR) = 50.83, 95% CI, 3.64-706.75, p = 0.003) and fluid deficit (AOR = 1.003, 95% CI, 1.000-1.006, p = 0.044) had a higher likelihood of an unsuccessful outcome. Hysterectomy was performed in 47.8% of patients who had failure of the ablation. Conclusions: Among pre-operative factors, adenomyosis, fluid deficit and combined adenomyosis and dysmenorrhea were found to predict failure of hysteroscopic endometrial ablation. Clinical Trial Registration: It was registered in https://www.clinicaltrials.gov database with Identifier: NCT05483348.